The Lecturers’ Perception of Digital Games-Based Language Learning at Higher Education - Mustari, Sri Hariati; Noni, Nurdin; Salija, Kisman; Sulaiman, Iskandar; Sakkir, Geminastiti (ELT Worldwide: Journal of English Language Teaching, 2025)
Digital learning has become a potential learning tool since the COVID-19 pandemic that has caused the use of new technologies including digital games-based language learning. However, the implementation still has different challenges due to technical, instructional and financial barriers. Previous studies suggest exploring more teaching experiences related to the use of digital games-based language learning for future contribution.  This study aims to explore the perception of the lecturers on digital games-based language learning in higher education. To achieve this goal, this study was conducted in an Indonesian higher education, the State University of Makassar by applying a qualitative case study to collect data. The researcher collected the data from 2 lecturers recruited using a convenient sampling technique. The thematic analysis was used to analyze the collected data.  This study explores teacher experiences in using digital games-based language learning in a speaking classroom. This study found that the lecturers perceived that Digital Games-Based Language learning (DGBLL) is useful, easy to use, and have a positive attitude toward its use. From this result, it is claimed academically that digital games-based language learning (DGBLL) can be used in speaking classrooms and modified based on learning objectives, learning outcomes and students’ learning needs.